The Effect of pH dependent and pH independent polymers on the drug release of anti-ischemic agent : Development and Characterization of Ranolazine ER Tablets - Gunda, Dr. Raghavendra Kumar; Manchineni, Prasada Rao; Kotcherla, Anil Kumar; Dhachinamoorthi, D.; Koteswara Rao, GSN (International Pharmacy Acta, 2021)
The objective of current study is to study the effects of combination of pH independent (HPMCK100M) and dependent (partially neutralized; Eudragit L 100-55) polymers on the drug release of Ranolazine form extended release tablet formulation. Ranolazine, an anti-ischemic or anginal agent. Mainly used for treating exercise induced; variant and stable chronic angina pectoris along with myocardial infarction. Anti-ischemic effect exhibited by Ranolazine is independent of haemodynamic effects, due to this benefit; it was useful for treating patients, who were not responded to other anti-anginals. Extended release tablets of Ranolazine were prepared using various proportions of Eudragit L 100-55,HPMCK100M in by direct compression technique. 9 formulations were developed and characterized for pharmacopoeial limits. Data obtained from the dissolution study fitted well to kinetic modeling, kinetic parameters were determined. EHR5 containing 31.25 mg of Eudragit L 100-55& 31.25 mg of HPMCK100M, is the best formulation showing similarity f2=85.77, f1= 2.31 with the marketed product (RANOLAZ). Formulation EHR5 follow zero order, whereas release mechanism found to be nonfickian type (n= 0.653).